Simply lies - Baldacci, David (GCP, Grand Central, 2023)
"Two women--a former detective and a dangerous con artist--go head-to-head in a twisting game of cat and mouse"--
Following a disastrous divorce, former New Jersey detective Mickey Gibson is now employed by a global investigation company, ProEye, to track down some of the extremely wealthy who seem bent on not paying their debts. Mickey misses police work but it has no place for her new role as the sole carer of two small children. When Mickey is asked by Arlene Robinson, a colleague from ProEye, to inventory an old mansion owned by a notorious former arms dealer, Rutger Novak, she discovers a long-decomposed body in a secret room. Apparently, Novak has cheated ProEye clients out of millions in the past and now they want to nail him. As the police investigation begins, they discover that there is no Arlene Robinson working for ProEye. Nor is there a mansion allegedly belonging to Novak. And the dead man is named as local wealthy recluse Daniel Pottinger. Now begins an unusual and compelling cat-and-mouse contest between the two women - revealing more about Gibson, but much more about the woman with no name, no morals and no empathy, who seems to be able to convince anyone of anything.
Keywords: Swindlers and swindling -- Fiction; Women detectives -- Fiction; Single mothers -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction